Analisis Perhitungan Harga Pokok Produksi Secara Tradisional Berdasarkan Pesanan Untuk Memperoleh Informasi Laba Rugi - Didik Kurniawan (Universitas 45 Surabaya, 2024)
This research aims to analyze traditional production cost calculations based on orders to obtain profit and loss information. As time goes by, many small companies still use traditional calculations of the cost of goods manufactured, but not according to orders, so these calculations are less accurate if used in the long term, which results in the profit and loss not being known for certain. Therefore, small businesses, especially the Kurnia Welding Workshop, should calculate the cost of production according to orders so that they obtain a profit or loss each year. The techniques used consist of observation, interviews and documentation. The results of this research show that the HPP calculation according to the Kurnia Las Workshop, especially for BOP and Non-Production Costs, is based on the owner's estimate, so the resulting HPP is less relevant and accurate. Determining the selling price according to the Kurnia Welding Workshop without calculating the cost of production first, is only based on the owner's estimate, which results in losses when the Kurnia Welding Workshop calculates the cost of production to produce a profit and loss report at the end of the period. Meanwhile, calculating the cost of production based on orders produces a HPP value that is smaller than the calculation for the Kurnia Welding Workshop because the costs are calculated according to the orders received. Meanwhile, in determining the selling price, it is calculated by adding the desired profit after calculating the COGS, so that when preparing the profit and loss report at the end of the period, the Kurnia Welding Workshop makes a profit.